The Historic Center of Lima: conservation versus inappropiate use of 'minor' architectural heritage - Lombardi, Angela (2018)
The historic center of Lima is a cultural heritage of great interest, currently in an advanced state of decay and in need of an appropriate and effective protection. This article concerns a presentation given in Lima for the “V Jornadas de Conservación y Restauración” organized by Yachay Wasi (Instituto Superior de Conservación y Restauración) on August 30-31, 2013, later implemented by new research advancements on the analysis of residential buildings and urban fabric transformation. Research first phase has developed a methodological approach whose goal was the identification of endagered heritage, prior to every rehabilitation program. Second phase, in course of development, concerns themes related to the widening of the concept of ‘cultural heritage’, which arises the issue of preserving ‘minor’ architectural heritage, shaping the features of the space of the old city of Lima. In the study a survey form was developed which fully describes the significance and the level of risk of historic structures, gathering and coordinating highly diverse data related to architectural scale and to relationship with the city. The analysis form is here utilized to assess the conservation of minor architecture with the purpose of proposing an effective rehabilitation strategy and a social and sustainable adaptive reuse.